Carmelo Bene e Carlo Sini: la resa dei conti con il linguaggio - Sergio Fava (Mimesis Journal, 2017)
This text by Sergio Fava is the re-proposal of his relation with the same title held at the Conference “Le arti del ‘900 e Carmelo Bene”, curated by Edoardo Fadini, Turin, 24-26 October 2002.